The Correlation of Sleep Patterns toward Student Academic Ability of the Pre-Clinic Students - Taqiyuddin, Naufal; Salsabila, Adinda Firyal; Rahmadhani, Desintya; Nabila, Jihan; Dwipo, Aryo Kusumo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Some studies suggest that one-third of adults experience poor sleep habits. Students are one of them, this is because students experience stress due to academic burdens changing sleep patterns and affecting student academic ability.Objective: To determine the correlation between sleep patterns and academic abilities.Methods: The research design used was cross-sectional using a self-administered Google form questionnaire given to students of the Faculty of Dental Medicine, Universitas Airlangga, from the third and fifth semesters through social media.Results: This questionnaire was filled in by 100 respondents (49 respondents from the third-semester student and 51 respondents from the fifth-semester students). As many as 91 students had less sleep duration (